Decomposition of global value chains for equipment exports of China - Zhang, Wei; Yong, Chen Chen (Institute of China Studies, University of Malaya, 2018)
Traditional trade statistics on gross trade is clouded by double counting of trade in intermediates across national borders. The value-added statistical method provides clarity to such situations which decomposes the global value chains (GVC) of exports. We have examined China’s equipment manufacturing products trade by adopting value-added statistical method based on Wang, Wei and Zhu (2013). The decomposition results show a dominant share of domestic value-added (DVA), a small share of foreign value-added (FVA), a tiny share of returned domestic value-added (RDV), and pure double counting (PDC). This indicates that the exports of China’s equipment products are mainly final products. Moreover, the results of participation and position indices show a stable participation trend and an upward trend in GVC respectively. Comparing with five selected countries, China’s equipment industry participation in GVC is moderate and belongs to downstream industries.